2006
DOI: 10.1111/j.1472-765x.2006.01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular level damages of low power pulsed laser radiation in a marine bacterium Pseudoalteromonas carrageenovora

Abstract: Aim:  To study the molecular level damages in a marine bacterium, Pseudoalteromonas carrageenovora, exposed to low power pulsed laser radiation from an Nd:YAG laser. Methods and Results:  The laser damages in bacterial DNA were monitored by studying the formation of apurinic/apyrimidinic (AP) sites. Molecular probe kits were used for this purpose. Occurrence of lesions in the cell walls was monitored under a transmission electron microscope (TEM). The results showed that laser radiation significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The reason for the difference in the mortality rates in these two types of radiation is undoubtedly due to the difference in the mechanisms of action these types of radiation have on the microbial cells. Visible laser light in the low power region results in the generation of reactive radicals (Wilson, 1993), and might result in the breakage of cell walls and generation of apurinic-apyrimidinic sites in the bacterial DNA (Nandakumar et al, 2005). These changes would lead to cell damage and death.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the difference in the mortality rates in these two types of radiation is undoubtedly due to the difference in the mechanisms of action these types of radiation have on the microbial cells. Visible laser light in the low power region results in the generation of reactive radicals (Wilson, 1993), and might result in the breakage of cell walls and generation of apurinic-apyrimidinic sites in the bacterial DNA (Nandakumar et al, 2005). These changes would lead to cell damage and death.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological analysis showed that the levels of infection and the bacterial count decreased significantly in the treated groups. According to Nandakumar et al [11], bacterial killing is related to cell wall damage and genetic material, reducing bacterial adherence and preventing biofilm formation [10]. Karu [32] relates the cytotoxic action to the production of highly reactive molecules that cause membrane rupture and subsequent bacterial death.…”
Section: Discussionmentioning
confidence: 99%
“…This physical feature has helped in controlling chemical mediators that play an important role in generating the inflammatory process, such as reduced expression of COX-2 [4], decrease in concentration of prostaglandin E 2 (PGE 2 ) [5], analgesia by the peripheral release of endogenous opioids [6], and edema reduction and anti-inflammatory action probably due to the release of adrenal hormones [7]. However, the use of lasers in the presence of an infectious process has not been well elucidated in the literature, as there is still a controversy regarding low-power laser on bacterial growth, concerning its parameters of use, such as wavelength, power, irradiation dose, type of laser, and effects on different bacterial strains [811]. Thus, although some studies show innocuous in relation to the increase of bacterial colonies subjected to laser application [12, 13], others demonstrate bactericidal and/or bacteriostatic effects [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of cultural heritage, it is a well established technique, allowing fine and selective removal of superficial deposits and encrustations [10,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Laser irradiation can be used for antifouling purposes, causing mortality to biofilm forming microorganisms, like marine bacteria and microalgae [26,27]. When applied to the treatment of lichen encrustations on stone, and although laser cleaning fails to completely remove lichen thalli, superficial lichen debris can be brushed away without affecting the substrate surface [10,28,29].…”
Section: Introductionmentioning
confidence: 99%